1997
DOI: 10.1080/0028825x.1987.10410176
|View full text |Cite
|
Sign up to set email alerts
|

Clematis vitalbain a New Zealand native forest remnant: does seed germination explain distribution?

Abstract: The pattern of distribution of the invasive vine Clematis vitalba in a typical New Zealand native forest remnant and the influence of chilling duration (chilling), nitrate (NO3-), and light on germination of C. vitalba were investigated. In the forest remnant, C. vitalba was not established in undisturbed forest where light levels were <3% full sunlight and rarely established where light levels were <5%. Clematis vitalba was, however, established in forest gaps and margins where light levels exceeded 5%, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
(15 reference statements)
1
19
0
1
Order By: Relevance
“…In particular, untreated (0) and DAR seeds needed 72 days to reach 50% germination (T 50 . This indicates that a certain degree of dormancy could be found in the study species, which is consistent with previous reports (Bungard et al 1997;Rudolf 1974;Van Gardingen 1986;West 1992). Moreover, it is widely reported that cold, moist incubation and/or GA 3 treatment promote completion of germination in dormant seeds (e.g., Baskin and Baskin 2014; Finch-Savage and Leubner-Metzger 2006), especially in temperate species, for which moist chilling is considered to be an effective mechanism that delays seed germination until after winter when conditions are more favourable for plant establishment (Bewley and Black 1985).…”
Section: Seed Germination Rate Under Alternating Temperature Regimessupporting
confidence: 81%
“…In particular, untreated (0) and DAR seeds needed 72 days to reach 50% germination (T 50 . This indicates that a certain degree of dormancy could be found in the study species, which is consistent with previous reports (Bungard et al 1997;Rudolf 1974;Van Gardingen 1986;West 1992). Moreover, it is widely reported that cold, moist incubation and/or GA 3 treatment promote completion of germination in dormant seeds (e.g., Baskin and Baskin 2014; Finch-Savage and Leubner-Metzger 2006), especially in temperate species, for which moist chilling is considered to be an effective mechanism that delays seed germination until after winter when conditions are more favourable for plant establishment (Bewley and Black 1985).…”
Section: Seed Germination Rate Under Alternating Temperature Regimessupporting
confidence: 81%
“…In New Zealand, the introduced vine Clematis vitalba is a major weed in native forest remnants. In these remnants, C. vitalba does not establish within Downloaded by [162.244.26.76] at 11:36 06 June 2016 undisturbed forest but instead tends to establish in forest gaps and forest margins, particularly when these areas have been subject to recent disturbance (Atkinson 1984;Bungard et al 1997a). Compared with the understory of undisturbed forest, forest gaps and margins have elevated irradiance, and soils that have been subject to recent disturbance often have elevated levels of soil NO3- (Haynes 1986;McDonald & Norton 1993;Bungard et al 1997a).…”
Section: Introductionmentioning
confidence: 98%
“…In these remnants, C. vitalba does not establish within Downloaded by [162.244.26.76] at 11:36 06 June 2016 undisturbed forest but instead tends to establish in forest gaps and forest margins, particularly when these areas have been subject to recent disturbance (Atkinson 1984;Bungard et al 1997a). Compared with the understory of undisturbed forest, forest gaps and margins have elevated irradiance, and soils that have been subject to recent disturbance often have elevated levels of soil NO3- (Haynes 1986;McDonald & Norton 1993;Bungard et al 1997a). Establishment of C. vitalba in forest gaps and margins, rather than in undisturbed forest, is consistent with reports suggesting that C. vitalba is adapted to high irradiance environments and that low irradiance may be a major factor limiting the distribution in forest remnants (Atkinson 1984;Van Gardingen 1986;West 1992).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, many studies that have examined the influence of different treatments, such as gibberellins (McDonough 1970), scarification (Pelton 1956), stratifications (Cavieres and Arroyo 2000) on seed germination of such alpine species, have pointed towards important role of dormancy in reproductive success of plants. For example, a chilling requirement can effectively regulate the timing of seed germination (Bungard et al 1997) and germination response to NO 3 -and/or light may be important as a gap or disturbance detection mechanism (Pons 1992). Thus, the study of dormancy mechanisms and germination requirements of alpine endemic species offers the prospect of understanding the survival advantages of dormant over-wintering seeds and also the role of seed germination in augmentation of restoration efforts urgently required for salvaging the critically endangered endemic species from extirpation and extinction.…”
Section: Introductionmentioning
confidence: 99%